Visible and near-infrared modulating tungsten suboxide nanorods electrochromic films in acidic aqueous electrolytes - Keechul Kwon; Jae Hun Lee; Kihoon Kim; Sungyeon Heo (Heliyon, 2024)
Proton-based aqueous electrolytes can be used to achieve high performance electrochromic nanocrystal thin films due to their small ion size. However, acidic aqueous electrolyte systems have not yet been explored in near-infrared (NIR) absorbing plasmonic tungsten oxide nanocrystal films. Here, we demonstrate tungsten suboxide nanorod films with excellent visible and NIR modulation performance in the H+-based aqueous electrolytes, thanks to their mesoporous structure, nanosized domains, and open tunnel structure. Colloidally synthesized WO2.83 nanorods with an average width of 6 nm and length of 48 nm were converted to WO2.90 nanorod film via annealing in air, while still preserving open tunnels. These films exhibit fast switching speed (tc = 0.9 s, tb = 2.1 s), excellent cycling stability over 2500 cycles, wide optical modulation up to ΔT = 53.8 % in the NIR region, and a high coloration efficiency (CE) of 167 cm2 C⁻1 at 1300 nm. Additionally, introducing a thin spacer (25 μm) reduced intrinsic NIR absorption from water, thereby enhancing the NIR modulation properties. These highly performing aqueous proton-electrolytes-based electrochromic devices open new possibilities for implementing visible and NIR electrochromism.